(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Woman constitutes the family, which leads to Society and Nation. Female entrepreneurs make significant contributions to economic growth and to poverty reduction. This conceptual paper indicates the role and emphasizes the women entrepreneurs as the potentially emerging human resource in the 21st century to overcome the economic challenges in global perspective. This paper conducts a study that is categories into three sections: First section based on performance and role of women entrepreneurs and SWOT Analysis. Increased female entrepreneurial activity heralds a progress for women’s rights and optimization of their economic and social living index. Women entrepreneurship is synonymous with women empowerment. Parallel to the male counterparts, female entrepreneurs are catalytic in job creation, innovation and more than tangible contribution to the GNP of the country. An economy thrives when women get a level playing field as men. Innovation works as a catalyst or an instrument for Entrepreneurship. Indian Women, despite all the social hurdles stand tall from the rest of the crowd and are applauded for their achievements in their respective field. The transformation of social fabric of the Indian society, in terms of increased educational status of women and varied aspirations for better living, necessitated a change in the life style of Indian women. This paper endeavors to explore studies related to Women Entrepreneurship and Innovation in India.